Excellence in sport: Towards an understanding of the psychological "architecture" of elite athletes - L.S. Almeida; J.F.A. Cruz; D.S. Matos (Desafio Singular, 2011)
The purpose of this study was to provide a brief overview of the literature around the field of excellence, focused on the sport's context. Thus, the main approaches to the study of excellence were presented and then some important factors in its development and maintenance were sought considering a set of social and personal dimensions. Among the latter, the focus of attention was on the athlete's psychological, motivational, affective, and emotional characteristics and skills, in an attempt to design the elite athletes' psychological "architecture". The characterization of these athletes included a number of consensual factors and strategies, such as high levels of motivation, commitment, concentration, and self-confidence, as well as the use of adaptive coping strategies, self-regulation, goal-setting and mental imagery. Although these results show some consistency in terms of research, it is still unsolved the issue of the weight and importance of each one of these factors and how such factors are combined in order to "produce" excellent performances.